2017
DOI: 10.32607/20758251-2017-9-2-4-16
|View full text |Cite
|
Sign up to set email alerts
|

At the Interface of Three Nucleic Acids: The Role of RNA-Binding Proteins and Poly(ADP-ribose) in DNA Repair

Abstract: RNA-binding proteins (RBPs) regulate RNA metabolism, from synthesis to decay. When bound to RNA, RBPs act as guardians of the genome integrity at different levels, from DNA damage prevention to the post-transcriptional regulation of gene expression. Recently, RBPs have been shown to participate in DNA repair. This fact is of special interest as DNA repair pathways do not generally involve RNA. DNA damage in higher organisms triggers the formation of the RNA-like polymer – poly(ADP-ribose) (PAR). Nucleic acid-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 194 publications
(226 reference statements)
0
9
0
Order By: Relevance
“…39,43 A role for FOXL2 in these crucial processes is supported by its interaction with HNRNPUL2 (Heterogeneous Nuclear Ribonucleoprotein U-like Protein 2), which promotes DNA double strand break signaling and repair 44 and with the helicase XRCC6 (KU70) involved in double strand DNA repair 45,46 and probably in telomeric stability. [50][51][52] ESR1 is a known FOXL2 co-factor, 20 and our MS data identify other major actors of this process: TOP2B, XRCC6, RNA Pol II (eight subunits of the RNA polymerase II holoenzyme complex), F I G U R E 6 Analysis of alternative splicing events (ASEs) upon FOXL2 knockdown. We have previously shown that the interaction of XRCC6 with FOXL2 leads to an inhibition of the transactivation ability of the latter on several reporter promoters and its apoptosis-inducing capacity, suggesting a potential implication in granulosa cell tumorigenesis.…”
Section: Discussionmentioning
confidence: 83%
“…39,43 A role for FOXL2 in these crucial processes is supported by its interaction with HNRNPUL2 (Heterogeneous Nuclear Ribonucleoprotein U-like Protein 2), which promotes DNA double strand break signaling and repair 44 and with the helicase XRCC6 (KU70) involved in double strand DNA repair 45,46 and probably in telomeric stability. [50][51][52] ESR1 is a known FOXL2 co-factor, 20 and our MS data identify other major actors of this process: TOP2B, XRCC6, RNA Pol II (eight subunits of the RNA polymerase II holoenzyme complex), F I G U R E 6 Analysis of alternative splicing events (ASEs) upon FOXL2 knockdown. We have previously shown that the interaction of XRCC6 with FOXL2 leads to an inhibition of the transactivation ability of the latter on several reporter promoters and its apoptosis-inducing capacity, suggesting a potential implication in granulosa cell tumorigenesis.…”
Section: Discussionmentioning
confidence: 83%
“…All these events have to be regulated by protein-DNA and protein-protein interactions as well as by interactions of proteins with poly(ADP-ribose). It is known that the function of RNA-binding proteins is also dependent on PARP and poly(ADP-ribosyl)ation (27,114).…”
Section: Discussionmentioning
confidence: 99%
“…PARP1 could be activated by phosphorylation (594), by direct protein/protein interaction (595), and by ADP-ribosylation by PARP3 (45). An interaction with YB-1 was shown to control the level of PARylation depending on the significance of DNA damage (596). The full biological significance and molecular mechanisms of these alternate roles remain to be elucidated.…”
Section: Coupling Dna Damage Detection To Catalytic Activitymentioning
confidence: 99%